The Relationship Between the Precipitation and the Flow in the Qias River Basin - عمار غطفان; علي صفاء (Latakia University Journal -Engineering Sciences Series, 2021)
Water is the secret of the life, the most important natural resource ever and the indispensable nerve of life, where water issue is considered the most important matter in our age in all fields and the increasing demand for water with the rise in development rate are the most significant modern challenges. The Qias River lies to the east Tartarus city and is considered the biggest tributary of the river Husain. It is an ever-flowing river. The area of its basin is 65.68 km² and the length of its course is 16.55km. The study aims to find relationship between rainfall and flow within Oias River Basin, by conducting analytical statistical study using Minitab software, which helps in completing the measurements are not available, and to predict the river flows depending on the expected precipitation in the river basin. The study found that the relationship is: Flow=-44.87+6.87ln (precipitation) ,and rainfall reflect 88.6% of the changes that occur to the flow of the river. The research has recommended the use of the artificial intelligence technologies in the management of the water resources in the study area.